Tree component analysis in a savanna-forest ecotone area of Minas Gerais State, Brazil - Dias Cabacinha , Christian; Guimarães Pereira, Kelly Marianne; Gomes Cordeiro, Natielle; Santos Fonseca, Rúbia; Araújo Júnior, Carlos Alberto (Scientia Agraria Paranaensis, 2021)
Ecotones are transition areas characterized by environmental complexity and high biodiversity. In this sense, carrying out a floristic survey and characterization of each phytoecological region is necessary. Thus, we analyzed the floristic composition, horizontal and vertical structure, and dispersal syndromes of the woody community in an ecotone of Cerrado Sensu Stricto and seasonal deciduous forest. Likewise, we proceeded with the floristic similarity analysis to evaluate the study area’s similarities to the vegetation of cerrado Sensu Stricto and seasonal deciduous forest. A total of 919 individuals from 19 families, 43 genera, and 49 species were sampled. The tree community has an average height of 4.12 m, a species diversity of 3.03 nats ind‑1, and a Pielou equitability index of 0.77. The predominant dispersion syndrome was anemochory. The vegetation formed floristic groups with the Cerrado Sensu Stricto. The environmental gradient that determines the occurrence of transition vegetation makes each remnant unique in terms of species and structure, demonstrating the importance of these areas for the biodiversity conservation.